Improving The Student Learning Outcomes Through Public Relation Administration Module Development Based on POE Protocol - Yurikhe Indah Ayuning Puspa; Lulu Nurul Istanti; Imam Muchayat (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2017)
The purpose of this research is to produce module of Public Relation and Protocol Administration based on POE for Eleventh Grade Office Administration 2 which has been tested its validity and to know the improvement of student learning outcomes after using this module. This type of research is research and development with using Borg & Gall model. Research indicates that the module of Public Relations and Protocol Administration using POE model have been validated and the result is feasible to be used and the student’s learning outcomes in the experimental class are higher than the control class.